NuminaMath 7B: Revolutionizing Math Solving with Integrated Reasoning Advanced Generative AI Tools and Python REPL - Jufriansah, Adi; Akib, Irwan; Ishartono, Naufal; Khusnani, Azmi; Rahmawati, Tanti Diyah; Malahina, Edwin Ariesto Umbu; Maure, Osniman Paulina; Romadloni, Nova Tri (Jurnal Penelitian Sains Teknologi, 2026)
The efficacy of NuminaMath 7B, an AI model that was created to address mathematical challenges, is assessed in this investigation. We evaluated the model's accuracy and efficiency against conventional methods through experiments that produced quantitative data. Qualitative data were collected through surveys and interviews with users to gain insight into their experiences and pinpoint areas for improvement. The survey results indicated that users found NuminaMath 7B to be pertinent, effective, and user-friendly, as evidenced by the exceptionally high average scores in user experience (95), perception of features and interface (90), and additional feedback (85). NuminaMath 7B was able to offer mathematical solutions with logical and detailed explanations as a result of the model's development through two phases of adjustments, which were conducted using the Chain of Thought (CoT) methodology and inspiration from the Tool-Integrated Reasoning Agent (ToRA) framework. Testing demonstrated that the model achieved a score of 29 out of 50 in the AI Math Olympiad competition, despite encountering difficulties in resolving more intricate problems. This study underscores the significance and urgency of AI technology, particularly in the field of mathematics, as well as the significant potential of AI models to facilitate a more comprehensive comprehension of mathematical concepts.